Penguatan Tata Kelola Koperasi Desa Merah Putih melalui Optimalisasi Manajemen Keuangan dan Pelayanan Anggota di Desa Nekmese - Indriyati Indriyati; Hendrikus L. Kaha; Petrus Alnimas; Yulius Yasinto; Yustina Alfira Nay (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2026)
The limited managerial capacity of the administrators of the Merah Putih Village Cooperative in Nekmese Village has become a major challenge in establishing effective and sustainable cooperative governance. This community service program aimed to strengthen cooperative governance by improving the administrators’ competencies in financial management and member services. The program was conducted through a participatory approach consisting of needs assessment, training, interactive discussions, and technical mentoring involving cooperative administrators, supervisors, and village officials. The training covered cooperative governance principles, financial administration, organizational management, strategic business planning, and member service improvement. The implementation results showed increased understanding among participants regarding financial recording, preparation of work plans, organizational governance, and strategies for developing cooperative business units based on local resources. Participants also demonstrated improved awareness of the importance of transparency, accountability, and member-oriented services as the foundation of sustainable cooperative management. The activity further identified the need for continuous mentoring, institutional strengthening, and digital-based administrative support to ensure the long-term effectiveness of the cooperative. Overall, the program contributed to enhancing the managerial capacity of cooperative administrators and provided a practical foundation for strengthening the institutional performance of the Merah Putih Village Cooperative in Nekmese Village.